Curcumin Alleviates Palmitic Acid-Induced LOX-1 Upregulation by Suppressing Endoplasmic Reticulum Stress in HUVECs. (23rd August 2021) - Luo, Ruixi; Zhao, Lifeng; Li, Shuaishuai; Chen, Peng; Wang, La; Yu, Honghong; Cai, Kun; Yu, Qi; Tian, Weiyi
Abstract : Excessive free fatty acid- (FFA-) induced endothelial lipotoxicity is involved in the pathogenesis of atherosclerosis. Endoplasmic reticulum (ER) stress is mechanistically related to endothelial lipotoxicity. Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) is the major oxidatively modified low-density lipoprotein (OxLDL) receptor in endothelial cells and is highly abundant in atherosclerotic lesions. Curcumin reduces the LOX-1 expression; however, the mechanism underlying this effect remains unknown. In the current study, we explored whether curcumin ameliorates palmitic acid- (PA-) induced endothelial lipotoxicity and LOX-1 upregulation by reducing ER stress in human umbilical vein endothelial cells (HUVECs). We built endothelial lipotoxicity in vitro and found that LOX-1 was upregulated after PA stimulation, during which ER stress played an important role. Next, we observed that curcumin substantially alleviated PA-induced lipotoxicity by restoring cell viability, increasing angiogenesis, and decreasing lipid deposition. Furthermore, LOX-1 upregulation in HUVECs was blocked by curcumin, possibly via ER stress suppression. Overall, our findings demonstrated that curcumin alleviates endothelial lipotoxicity and LOX-1 upregulation, and ER stress inhibition may play a critical role in this effect.